Conservação ex situ e aplicação dos descritores mínimos na caracterização de germoplasma de jenipapeiro - Santos, Cleverton Alves dos (2022)
Jenipapo (Genipa americana L.) is a plant native to Brazil, has wide use and is still cultivated in an extractive way. The fresh fruits are used in human food, in the manufacture of sweets, jam, juice, soft drinks, wine and brandy. This study aims to evaluate the accessions of the Jenipapo Genebank of Embrapa Tabuleiros Costeiros (Jenipapo Genebank) using morphoagronomic descriptors. The Genebank is located in the municipality of Nossa Senhora das Dores - SE, and is composed of 28 accessions represented by 254 plants. In obtaining the data, the characteristics of the stem, leaves, crown and presence of fruits were observed and measured, as well as the indices of crown proportion, degree of slenderness, salience index, coverage and crown formal and then they were coded in tables, obtaining a percentage of survival superior to 70% of the individuals. Specific characteristics of a single accession such as smooth trunk, presence of trichomes and distribution of horizontal branching were observed and the index results indicated accessions that present good vitality, stability, area quality and productivity. It was observed that accession AR3 had a higher proportion of the crown, demonstrating greater vitality. The use of descriptors minimal for the evaluation of the genebank was efficient and could direct future research in the area of genetic resources and plant breeding.